LIGNINE REMOTION FROM RICE HUSK PRETREATMENT BY STEAM EXPLOSION - Jorge Montalvo, Paola Aurelia (2019)
The present study evaluated the removal of lignin from the rice husk, by means of steam explosion at different severity conditions. The process of lignin removal was evaluated as lignin Klason was performed in samples with pretreatment at pressures of 0.4; 0.6; 0.8 and 1.0 MPa, times of 6, 8, 10 and 12 minutes with a decompression of between 5 to 7 seconds; it is a lignin removal from 18.02 % up to 12.7 % at 1.0 MPa and 12 min compression, factor of 3.3 severity. The evaluation by FTIR of the husk without pretreatment, with pretreatment at 0.4 MPa and 12 min, 1.0 MPa and 12 min, shows a reduction in the transmission generated by the peaks corresponding to the presence of lignin -OH (2920 cm-1 ), CH and CO (1320 and 1360 cm-1), COC a (1060 cm-1) among others. The promover per screening electronic microscopy (SEM) showed the degree of introducción Sud cantidades of the surface of the rice associated with theollowing of the lignin explicar. The pretreatment of the steam explosion of the rice husk improves the potential of rice husk hydrolysis for the formation of reducing sugars that can be exploited in the production of G-2 ethanol, due to the removal of lignin and the exposure of cellulose and hemicellulose.